Comparative analysis of parasternal lymph collector exposures in the organ-sparing treatment of patients with operable breast cancer - V. A. Uimanov (Opuholi Ženskoj Reproduktivnoj Sistemy, 2014)
The paper presents the results of a follow-up of 593 patients with the internal and central localization of clinical stages I-IIb breast cancer whose treatment comprises parasternal treatment techniques: teleradiotherapy (TRT), intratissue radiotherapy (ITRT), and video-assisted thoracoscopic parasternal lymphadenectomy (VAPL). A control group included 846 patients with the external localiza- tion of a tumor. There was a statistically significant increase in 5-year overall (98.2%) and relapse-free (96.2%) survival rates in Stage I in the VAPL versus TRT and ITRT groups (overall survival, 92.5 and 89.7%; relapse-free survival, 80.8 and 73.4%, respectively) (p < 0.05). There was no difference in survival rates between the study and control groups. It is concluded that VAPL permits the objective staging of the disease and any therapeutic exposure of the parasternal area made survival rates similar in the study and control groups.